Permeable road pavement with subsurface precast micro-detention storage: A green pavement practice / Norazlina Bateni - Norazlina , Bateni (2020)
Green infrastructure practices are uniquely applicable to address the relationship between land use and water resources through the replication of the natural hydrological process within the landscape. Implementation of such practices, especially green pavement can significantly improve the rainfall-runoff responses, and thereby minimise the occurrence of flood hazards, which may lead to uncountable economic losses. Common permeable pavements are typically composed of fine-layered particles attributed to low porosity. In this study, an innovative permeable pavement with a micro-detention pond storage (PPDS) system is proposed. It is a modified type of interlocking block permeable pavement consisting of a hollow cylinder with a hexagonal cover at the top and bottom of the PPDS. The PPDS is designed with a void volume of 70% and a water storage capacity of 0.19 m3/m2. The system can serve as an alternative for green pavement application as it meets all the principal criteria, particularly integrating the permeable and porous pavement with void spaces to store and recycle stormwater, attenuate the peak discharge, etc. A rainfall simulator is used to test the profile of the hydrological pavement, such as the storage capacity, detention period, permeability rates and infiltration performance over various storm events. The system performance is verified via simulation of storm water management model (SWMM), a product of US environmental protection agency (USEPA). The observed performances indicate that the PPDS has met the basic hydrological design considerations, like those in the typical permeable pavement, from the perspective of permeability rates, infiltration capacity, storage and detention capability. A case study is then developed to assess the hydrological impacts of PPDS and compared it with the conventional road pavement and other types of permeable pavements, such as pervious concrete (PC) and permeable interlocking concrete pavers (PICP). The PPDS results in higher runoff reduction, the lowest runoff coefficients, and peak flowrate. It also demonstrates faster infiltration of rainfall into ground with a higher rate of infiltration loss in comparison to those recorded for PC and PICP. These results demonstrate the effectiveness of PPDS as a permeable pavement with the presence of subsurface micro-detention storage. Hence, it is concluded that PPDS is a better practice in minimising runoff for stormwater management.